Reshoring: A study on firm characteristics and influencing factors - Sunghoon Chung (Korea Development Institute (KDI), 2023)
Among multinational manufacturers, firms engaged in reshoring are typically smaller, laborintensive, less productive, and less experienced in overseas production. Moreover, despite receiving sizable government subsidies, the domestic investments by reshorers yield smaller employment impacts compared to similar-sized domesticonly counterparts. Therefore, incentivizing domestic investment for all firms, irrespective of their repatriation, would be more effective in meeting objectives such as stabilizing supply chains, maintaining domestic manufacturing competitiveness, and boosting employment. The solution to the challenges posed by the excessive globalization of production lies in localizing production activities rather than the firms themselves.
Keywords: 330